Music and Tactile Stimuli during Daily Milking Affect the Welfare and Productivity of Dairy Cows - dos Santos Lemes Lechuga, Karine Keyzy; Caldara, Fabiana Ribeiro; de Castro Burbarelli, Maria Fernanda; Odakura, Agnês Markiy; dos Ouros, Caio César; Garcia, Rodrigo Garófallo; Félix, Gisele Aparecida; de Lima Almeida Paz, Ibiara Correia [UNESP]; Oliveira dos Santos, Viviane Maria; Braz, Jaqueline Murback (MDPI, 2023)
The objective of this study was to evaluate the effects of tactile stimuli and music during daily milking on the productive, physiological, well-being, and health parameters of dairy cows. The experiment, which lasted 39 days, was conducted on a commercial farm with forty crossbred cows (age: 36 to 42 months; weight: 350 to 400 kg) distributed in a completely randomized design (2 × 2) via the following treatments: (Con)—cows not exposed to stimuli, (Tac)—cows exposed to tactile stimuli before milking, (Mus)—cows exposed to music during milking, (Tac+Mus)—cows exposed to both stimuli. In this study, classical music with a slow (75 to 107 BPM) and moderate tempo (90 to 100 BPM) was played, and tactile stimuli was provided manually using a flexible stick in the posterior region and udders of the cows. Cows not exposed to any of the stimuli had up to 41% higher residual milk quantity compared to those exposed to one of or both of the stimuli. The sound stimulus promoted an increase in milk letdown before the start of milking. Cows exposed to stimuli showed higher serotonin levels, indicating a beneficial effect on animal well-being. However, cows exposed to pre-milking tactile stimuli showed an increase in somatic cell count. Combining both techniques may have positive effects on milk productivity and well-being. However, using music alone may be more recommendable as it does not pose health risks.
Keywords: dairy cattle; environmental enrichment; human–animal interaction; serotonin